2016
DOI: 10.1177/2158244015625327
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Philanthropic Awareness in Clothing Disposal Behavior Among Young Malaysian Consumers

Abstract: Young consumers are the stylish shoppers who have a strong tendency to follow the latest fashion. With the rapid changes in the fashion trends, the overconsumption of clothing has had a significant environmental impact on society. Hence, there is a need to understand how young fashionable consumers are disposing their unwanted clothes. The survey was conducted among 205 young respondents, and the results show that clothing disposal behavior is affected by philanthropic awareness and mediated by the attitude to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Thus, the products sold should follow the trend. Wai Yee et al (2016) said that young consumers are stylish buyers who have a strong tendency to follow the latest fashion trend. Customer satisfaction acts as a variable that mediates CPV with Patronage Intention.…”
Section: Customer Perceived Value (Cpv)mentioning
confidence: 99%
“…Thus, the products sold should follow the trend. Wai Yee et al (2016) said that young consumers are stylish buyers who have a strong tendency to follow the latest fashion trend. Customer satisfaction acts as a variable that mediates CPV with Patronage Intention.…”
Section: Customer Perceived Value (Cpv)mentioning
confidence: 99%
“…However, consumers neither understand nor have knowledge regarding environmental issues that involve man-made fibre and cotton production (Birtwistle & Moore, 2007). The consumers are also deemed to not feel guilty when it comes to disposing expensive materials and are apparently less interested in matters related to ethics and social awareness (Yee, Hassan, & Ramayah, 2016). Recycle means torn materials are repaired, re-designed, or re-used (Ekström & Salomonson, 2014).…”
Section: Environmental Consequences Of Textilesmentioning
confidence: 99%
“…Five study results revealed that awareness of sustainable clothing and consumption is somewhat limited [92,100,[104][105][106]. Other studies [92,107], introducing concepts of sustainability and illustrating fashion retailers' responses to sustainability, found that even though participants showed some sustainable behaviours, the awareness of fashion sustainability was low.…”
Section: Awareness Of Sustainabilitymentioning
confidence: 99%
“…A study conducted in India by Norris [108] referred to the growing Indian consumer awareness of recycling as an environmentally friendly practice, as well as recycling as an ancient process that is even linked to reincarnation [108]. A quantitative study carried out in Malaysia by Yee et al [106] focused on the clothing disposal behaviour of young fashionable consumers and showed that it is affected by philanthropic awareness and somewhat by the attitude towards clothing disposal. The authors suggested that these insights could be used by the government and related authorities or organisations to develop strategies accordingly to foster consumer clothing recycling [106].…”
Section: Consumer Awareness Of Recycling and Disposalmentioning
confidence: 99%
See 1 more Smart Citation